6+7+1(n*5)=-12

Simple and best practice solution for 6+7+1(n*5)=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+7+1(n*5)=-12 equation:


Simplifying
6 + 7 + 1(n * 5) = -12

Reorder the terms for easier multiplication:
6 + 7 + 1(5n) = -12

Remove parenthesis around (5n)
6 + 7 + 1 * 5n = -12

Multiply 1 * 5
6 + 7 + 5n = -12

Combine like terms: 6 + 7 = 13
13 + 5n = -12

Solving
13 + 5n = -12

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + 5n = -12 + -13

Combine like terms: 13 + -13 = 0
0 + 5n = -12 + -13
5n = -12 + -13

Combine like terms: -12 + -13 = -25
5n = -25

Divide each side by '5'.
n = -5

Simplifying
n = -5

See similar equations:

| 5x^2+x+7=0 | | U/4=6.5 | | 12a+12b+2c+6c-4b-4a= | | ((16x)/((x^2)+6))=0 | | -7g=1 | | 12m^2-8m-15=0 | | 16x/((x^2)+6)=0 | | 1m^2-8m-15=0 | | 5x+22(x-2)=307 | | 3x/5-8=-11 | | 14p+17q+p-6q-5p= | | x+2y-2=0 | | (x/3)+7=6 | | 5n+8n=3+2n | | -4+1=23 | | 3/2x+3/2y=3/4 | | 2/3-x/3=7/15 | | -14+15x=16 | | (x/2)-8=-2 | | (x/5)+9=-1 | | 9x^3+12x^2=12x^2+36 | | -3m/5=9 | | 387=5x+297 | | 6cosx=7 | | 5y-2=8 | | y=5x+297 | | -4+-1=23 | | x-10/4=-16/4 | | x^4-3x^3-44x^2-72x-32=0 | | 0=16+0.00032x | | 6cosx-7=0 | | 3x+6x-9=5x-21x+21 |

Equations solver categories